Performance‐enhancement of high‐strength strain‐hardening cementitious composite by nano‐particles: Mechanism and property characterization. (12th February 2021) - Ding, Yao; Yu, Kequan; Mao, Weihao; Zhang, Shuo
Abstract: Nano‐SiO2 (NS), due to its prominent nucleation and pozzolanic effects, holds the promise to effectively enhance the tensile and compressive properties of high‐strength strain‐hardening cementitious composite (HS‐SHCC) at both early age (1d, 3d) and normal curing age (28d). The influence of nano‐SiO2 (NS) on the hydration, microstructure and mechanical properties of HS‐SHCC with different dosages (i.e., 0%, 1%, 2%, and 3% by mass of cement) were explored in this research. The nucleation effect of NS particles accelerated the hydration process, and the pozzolanic reaction tended to improve the hydration degree of matrix at the micro‐scale. The addition of NS particles decreased the porosity and refined the pore structure of the matrix. Single‐fiber pullout tests (meso‐scale) showed a remarkable improvement of interfacial bond stress with the incorporation of NS particles and consequently on the macro‐scale mechanical strengths enhancement of HS‐SHCC. The linkage between meso‐ and macro‐scale properties was established based on the micro‐mechanical model. The combination of filler effect, acceleration effect and pozzolanic reaction of NS particles enhanced the microstructures and mechanical properties of HS‐SHCC. The increase in compressive and tensile strength of NS‐modified HS‐SHCC could reach to 45% (1d) and 30% (1d), respectively, compared to those values of the reference specimen without NS addition. This research provided an effective way to enhance the tensile performance of HS‐SHCC, especially for the early‐age tensile property.